FENOMENA KESETARAAN GENDER DALAM KREDIT - Dwi Rachmina (Departemen Agribisnis, FEM-IPB, 2009)
Gender inequality still exists in Indonesia on various sectors. However, the Gender-related Development Index (GDI) and Gender Empowerment Measurement (GEM) showed an increasing trends in recent years. The increase in GDI and GEM index indicates the gender equality in education, labor and business opportunities. Meanwhile, the gender equality in access to credit and capital is still unclear. This paper discusses the gender issue in credit policy, accessibility and utilization in Indonesia using literature review. Gender factor is not explicitly considered in credit policy which means that men and women have the equality to obtain and utilize credit. In reality, the low proportion of women borrower indicates that women accessibility towards credit is lower than men. Increasing in women accessibility towards credit will bring positive effect, economically and socially, for the women themselves and their family. The important implication is that increasing in business opportunities and labor for women will increase the accessibility of women to credit.